Scabies outbreaks in ten care homes for elderly people: a prospective study of clinical features, epidemiology, and treatment outcomes. Issue 8 (August 2018) - Cassell, Jackie A; Middleton, Jo; Nalabanda, Ananth; Lanza, Stefania; Head, Michael G; Bostock, Jennifer; Hewitt, Kirsty; Jones, Christopher Iain; Darley, Charles; Karir, Simran; Walker, Stephen L
Summary: Background: Scabies outbreaks in residential and nursing care homes for elderly people are common, subject to diagnostic delay, and hard to control. We studied clinical features, epidemiology, and outcomes of outbreaks in the UK between 2014 and 2015. Methods: We did a prospective observational study in residential care homes for elderly people in southeast England that reported scabies outbreaks to Public Health England health protection teams. An outbreak was defined as two or more cases of scabies (in either residents or staff) at a single care home. All patients who provided informed consent were included; patients with dementia were included if a personal or nominated consultee (ie, a family member or nominated staff member) endorsed participation. Dermatology-trained physicians examined residents at initial clinical visits, which were followed by two mass treatments with topical scabicide as per local health protection team guidance. Follow-up clinical visits were held 6 weeks after initial visits. Scabies was diagnosed through pre-defined case definitions as definite, probable, or possible with dermatoscopy and microscopy as appropriate. Findings: 230 residents were examined in ten outbreaks between Jan 23, 2014, and April 13, 2015. Median age was 86·9 years (IQR 81·5–92·3), 174 (76%) were female, and 157 (68%) had dementia. 61 (27%) residents were diagnosed with definite, probable, or possible scabies, of whom three had crusted scabies. Physical signs differed substantially from classic presentations. 31 (51%) of the 61 people diagnosed with scabies were asymptomatic, and only 25 (41%) had burrows. Mites were visualised with dermatoscopy in seven (11%) patients, and further confirmed by microscopy in three (5%). 35 (57%) cases had signs of scabies only on areas of the body that would normally be covered. Dementia was the only risk factor for a scabies diagnosis that we identified (odds ratio 2·37 [95% CI 1·38–4·07]). At clinical follow-up, 50 people who were initially diagnosed with scabies were examined. No new cases of scabies were detected, but infestation persisted in ten people. Interpretation: Clinical presentation of scabies in elderly residents of care homes differs from classic descriptions familiar to clinicians. This difference probably contributes to delayed recognition and suboptimal management in this vulnerable group. Dermatoscopy and microscopy were of little value. Health-care workers should be aware of the different presentation of scabies in elderly people, and should do thorough examinations, particularly in people with dementia. Funding: Public Health England and British Skin Foundation.